QUALITATIVE ANALYSIS OF THE USE OF ANTIBIOTICS IN INDAPED PATIENTS AT PKU MUHAMMADIYAH HOSPITAL, WONOSOBO JANUARY-DECEMBER 2021 PERIOD - Noor Syam Sidiq Himawan; Lestari Wahyu Herawati; Artha Sudibyo; Chusna Yumnannisa (Proceedings of the 1st International Conference on Social Science (ICSS), 2022)
Disease infection is a disease that is still a health problem in Indonesia Indonesia. This is because the prescription of antibiotics is very high with the use of drugs that are too high no wise so that will Upgrade happening resistance. To describe the use of antibiotics qualitatively reviewed with method Gyssens in hospital PKU Muhammadiyah Wonosobo. Study this is study observational use data retrospective. subject The study consisted of inpatients at PKU Muhammadiyah Wonosobo Hospital who received therapy antibiotics in period January – December 2021. Use of antibiotics using qualitative methods from January to December 2021 there is 53 case patient which has observed, rated from the accuracy of the indication, the dose of antibiotics, duration gift, long gift, route, intervals gift and price antibiotics obtained results 74 % use antibiotics already correct/rational and 26 % prescription which still not yet right/irrational. Use antibiotics which rational could prevent happening antibiotic resistance. use which right/right will optimizing effectiveness antibiotics in hinder the development of good bacteria in the right indication, the right dose, the right administration, the right route that benefits in process service use therapy antibiotics which true/correct